Defending the Shore, Voicing the Right: Communication Strategies of the Save Pede Beach Movement: - Frederik Masri Gasa; Chininta Rizka Angelia; Ernestus Holivil; Everd S. R. Daniel (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2025)
This study aims to examine the social movement of the Labuan Bajo community, which is part of the Save Pantai Pede Movement, as a form of resistance to the privatization of public space by the provincial government and private investors. The primary issue in this study is the power imbalance in the management of public space, which contributes to the marginalization of local communities. This study employs a critical approach, utilizing Norman Fairclough's Critical Discourse Analysis and Pierre Bourdieu's theories of habitus, capital, and social field as analytical tools. Data were obtained through documentation studies, observations, and in-depth interviews, which were analyzed at three levels: textual, discourse practice, and sociocultural practice. The study's results show that the community, particularly young people and local artists, produces a discourse of resistance through art and public symbols that affirm public space as a shared right. This movement has succeeded in transforming the commercialization project into a broader public debate on spatial justice and community political participation. These findings confirm that community-based social movement can be an effective tool for political negotiation in addressing structural and capitalist domination of public space.